Recent advances and insights into the bioactive properties and applications of Rosa canina L. and its by-products - Oana-Raluca Negrean; Anca Corina Farcas; Silvia Amalia Nemes; Diana-Elena Cic; Sonia Ancuta Socaci (Heliyon, 2024)
Rosa canina L., commonly known as rosehip, is of notable scientific interest for its applications in nutrition, cosmetics, and pharmaceuticals. This review article highlights its health-promoting properties, including antioxidant, anti-inflammatory, hepatoprotective, and anticarcinogenic effects, attributed to its rich content of phenolic acids, carotenoids, tocopherols, and vitamins. With growing interest in sustainable practices, rosehip by-products are increasingly valorized. For instance, cold-pressed rosehip seed oil is a valuable source of polyunsaturated fatty acids, while incorporating rosehip pomace into snacks enhances their nutritional profile, positioning them as potential functional foods and dietary supplements. This article aims to provide a comprehensive overview of advancements in utilizing rosehip and its by-products, emphasizing their role in enriching food and pharmaceutical products with nutritional and functional bioactivities.